Surface Properties of a Pyrogenic Low Surface Area Silica: A Microcalorimetric and IR Spectroscopic Investigation - Vera Bolis; Leonardo Marchese; Salvatore Coluccia; Bice Fubini (Adsorption Science & Technology, 1988)
The affinity towards water of a pyrogenic low surface area silica (50 m 2 /g) has been studied by adsorption microcalorimetry and IR spectroscopy. Attention was given both to the dehydration and rehydration processes under different conditions. The evolution of OH species was investigated in the 298–1073 K range. Evidence has been obtained for two species; isolated free (3750 cm −1 ) and adjacent interacting (3670 cm −1 ) hydroxyls. The presence of isolated silanols (which are usually created at a silica surface by outgassing at T > 450 K) on the initial ‘virgin’ sample (i.e. prior to any thermal treatment) accounts for the intrinsically low hydrophilicity of this specimen. By raising the outgassing temperature, the extent of the 3750 cm −1 species increases in parallel with the disappearance of the 3670 cm −1 species. The progressive development of surface hydrophobicity was monitored by the decrease in the adsorption capacity and of the heat of adsorption, the latter falling far below 44 kJ/mol (latent heat of liquefaction of water) even for the sample treated at 423 K. Upon contact with water vapour at r.t., rehydration occurs only to a limited extent and depends on both the thermal pretreatment undergone by the sample and the time of exposure to H 2 O vapour.